Organizational theory : - Jones, Gareth R. (Addison-Wesley, 1995)
Comprehensive and current, the third edition of Organizational Theory makes important theories accessible and interesting in order to teach future managers the skills and concepts necessary to succeed. An integrated flow between chapters - allows students to clearly see how topics relate to each other from the start. Explanations of the most recent developments in organizational structure such as the product team structure, outsourcing, and the network organizations. Discussion of recent literature on inter-organizational linkage mechanisms, including the role of resource dependence theory and transaction cost theory in explaining why organizations choose different types of linkage mechanisms....